ESSENCE SYNC: PIONEERING PERSONALIZED WELLNESS TECHNOLOGY - Mr. Kiran H. Wagh; Mr. Samarth Mandrupkar; Mr. Nimish Vaddepalli; Mr. Pranav Pogul; Mr. Shubham Vidap (International Journal of Innovations in Engineering Research and Technology, 2024)
ESSENCESYNC is a revolutionary personalized wellness technology that uses sensors, real-time data analysis, and communication systems to revolutionize healthcare. The platform uses sensors like temperature, accelerometer, pulse, and ECG to track vital signs and health parameters. It provides actionable insights to users, allowing them to track progress over time. The platform also ensures timely communication of critical health information through SMS alerts. Its seamless integration with healthcare providers allows for remote monitoring and collaboration, facilitating early detection of health issues and personalized treatment strategies. The technology also ensures compliance with regulatory standards like HIPAA. ESSENCESYNC’s potential benefits extend beyond individual wellness, including enhanced doctor-patient communication, improved patient engagement, and early detection of health risks. Its continuous innovation and exploration of AI and machine learning algorithms further enhance its predictive capabilities.